Near-tip analysis of crack propagation in cementitious composites - Pereira, E. N. B. (2011)
The fracture process zone encloses relevant mechanisms which explain the quasi-brittle behavior of cementitious composites. It is an important concept in non-linear fracture mechanics and in the simulation of cracking processes. The use of fibers as reinforcement may alter the crack initiation and propagation processes. A better understanding of the micro-cracking mechanisms taking place at the level of the fracture process zone is therefore relevant for an optimized design of these materials, as well as for the simulation of their mechanical behavior. In this study, the use of an image analysis procedure to capture the crack initiation and propagation process in concrete and other cementitious composites is described. It utilizes high resolution digital images of the surface of the specimens while undergoing the cracking process to determine the displacement fields. The formed cracks are observed at a relatively small scale, allowing the investigation and analysis of propagating cracks near the crack tip in specimens of concrete and other cementitious composites.